2008
DOI: 10.1073/pnas.0808506106
|View full text |Cite
|
Sign up to set email alerts
|

CTCF-dependent enhancer-blocking by alternative chromatin loop formation

Abstract: The mechanism underlying enhancer-blocking by insulators is unclear. We explored the activity of human ␤-globin HS5, the orthologue of the CTCF-dependent chicken HS4 insulator. An extra copy of HS5 placed between the ␤-globin locus control region (LCR) and downstream genes on a transgene fulfills the classic predictions for an enhancer-blocker. Ectopic HS5 does not perturb the LCR but blocks gene activation by interfering with RNA pol II, activator and coactivator recruitment, and epigenetic modification at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
143
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(157 citation statements)
references
References 46 publications
(53 reference statements)
14
143
0
Order By: Relevance
“…S1). Importantly, the optimized ACME parameters identified peaks at the locus flanking β-globin HS5 and 3′HS1 sites where numerous reports have documented CTCF binding in vivo (10,13,16); these sites had not been consistently identified as peaks in earlier genome scans (17,18). In other respects, such as the degree of overlap in CTCF sites between cell types and the CTCF motif shared by the sites, there was a high level of agreement between this analysis and the earlier studies (Fig.…”
Section: Numerous Sites Of Ctcf Enrichment Reside Among Silent Olfactorysupporting
confidence: 75%
See 2 more Smart Citations
“…S1). Importantly, the optimized ACME parameters identified peaks at the locus flanking β-globin HS5 and 3′HS1 sites where numerous reports have documented CTCF binding in vivo (10,13,16); these sites had not been consistently identified as peaks in earlier genome scans (17,18). In other respects, such as the degree of overlap in CTCF sites between cell types and the CTCF motif shared by the sites, there was a high level of agreement between this analysis and the earlier studies (Fig.…”
Section: Numerous Sites Of Ctcf Enrichment Reside Among Silent Olfactorysupporting
confidence: 75%
“…The 3C assay was performed as described (13). Briefly, formaldehyde-fixed nuclei were digested with EcoRI to generate conveniently sized fragments, followed by ligation with T4 DNA ligase at 16°C for 4 h. Cross-links were reversed, and DNA was extensively purified before PCR amplification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancer-blocking insulators are defined by their ability to prevent enhancer activation of the promoter when placed between the enhancer and the promoter. A large body of evidence is consistent with the idea that insulators work by binding proteins that form DNA loops to other insulators (31)(32)(33)(34)(35). This mechanism of insulator action is rationalized by the loop domain model (36), which proposes that the formation of a DNA loop creates a separate topological domain that inhibits interaction between any site within the loop and any site outside the loop (Fig.…”
mentioning
confidence: 55%
“…Differential binding of the insulator protein CTCF could have a major influence on expression of distant genes through alternative loop formation, as has been observed in b-globin expression in mouse models. 33 A recent study has shown that loss of CTCF binding to a boundary region upstream of CDKN2A resulted in spreading of repressed chromatin and DNA methylation into the p16 promoter with sequential downregulation of p16 expression. 34 The same study described that loss of upstream CTCF binding resulted in promoter DNA methylation of RASSF1 and CDH1., 34 Contradictory to the finding that CTCF binding abrogation was shown to be causative of heterochromatin spreading and DNA methylation 34,35 is the observation that DNA methylation of CTCF binding sites is suggested to regulate CTCF binding.…”
Section: Discussionmentioning
confidence: 99%